Companion of the 2018 ACM Conference on Computer Supported Cooperative Work and Social Computing 2018
DOI: 10.1145/3272973.3274065
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Perceived Behavior Control and Emotional Labor on Gig Workers

Abstract: Gig economy workers enjoy flexibility in choosing certain aspects of their work. Nonetheless, platform companies still need to control workers' behaviors to scale their business and ensure customers quality service. Mechanisms of control have been widely studied in traditional organizations; however, work in the gig economy differs from traditional organizations in that the role of a human supervisor is replaced with digital systems. Thus, there is reason to suspect that our traditional theories of control may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…For better or for worse, AI management systems are based on theory X. AI management systems seek to promote worker engagement by directing, monitoring, and rewarding and/or punishing employee's actions. This approach is especially true for sharing economy platforms like Uber that enable the gig economy (Marquis et al, 2018). But, they can also be true for AI management systems in traditional organizations.…”
Section: Artificial Intelligence Employee Controlsmentioning
confidence: 99%
“…For better or for worse, AI management systems are based on theory X. AI management systems seek to promote worker engagement by directing, monitoring, and rewarding and/or punishing employee's actions. This approach is especially true for sharing economy platforms like Uber that enable the gig economy (Marquis et al, 2018). But, they can also be true for AI management systems in traditional organizations.…”
Section: Artificial Intelligence Employee Controlsmentioning
confidence: 99%
“…Emotional labor, the process of managing emotional expressions as part of one's work role, has been characterized as an inner feature of gig work. Research has shown that Uber and Lyft workers often find their work emotionally taxing (Malin & Chandler, 2017) because they have to engage in emotional labor to gain favorable customer ratings (Grandey & Gabriel, 2015; Marquis et al, 2018). Based on interviews with Uber and Lyft drivers, Ladegaard et al (2022) found that drivers had to deal with their emotions of fear, disgust, anger and worries due to the diverse threats they faced, such as verbal abuse, safety concerns, and potential for low ratings.…”
Section: Themes and Issues In The Gig Work Literaturementioning
confidence: 99%
“…What's more, algorithmic management leaves workers fearful of unexplained bans, gamification tactics atomize workers by encouraging competition rather than collaboration, and ruthless data-driven profit optimization leaves workers too financially precarious to risk losing income due to platform retribution [40].…”
Section: Platform Work Algorithmic Management and The Complications O...mentioning
confidence: 99%